Primipaternity in multiparas as a predominant high risk factor for preeclampsia over prolonged birth intervals: A study of 33,000 singleton pregnancies in Reunion Island. - Pierre-Yves Robillard; Silvia Iacobelli; Simon Lorrain; Francesco Bonsante; Malik Boukerrou; Marco Scioscia; Phuong Lien Tran; Gustaaf Dekker (PLoS ONE)
Objectives To evaluate the relative importance of changing paternity ("primipaternity", direct inquiry with patients) in multiparas versus prolonged birth/pregnancy interval as risk factors for preeclampsia (PE) by a logistic regression model comparing the adjusted odds ratios of both exposures. Design Assessment of all consecutive singleton deliveries (from 22 weeks onwards) at South-Reunion University's maternity (Reunion Island, Indian Ocean) over 23 years (2001-2023) using an epidemiological perinatal database on obstetrical factors (264 items in total, of which, chronic or gestational hypertension, proteinuria, HELLP syndrome). Results Among the 53,572 multiparous singleton pregnancies, we identified 33,312 (62%) of multiparas who gave consecutive births, allowing calculation of birth intervals. Primipaternity multipara (N = 2790) were on average older than those in stable relationships (N = 50,782), 31 vs 30 years, p< 0.0001; they had almost systematically longer birth intervals compared with controls of approximately 1.5 year from the 2nd to the 4th pregnancy and approximately 1year after the 5th pregnancy (all p < 0.05). In the logistic regression model of 11 risk factors, intervals between pregnancies had similar adjusted odds ratios (1.05, p = 0.002) as increasing maternal age (AdjOR 1.02, p = 0.02), increasing parity (adjOR 1.09, p = 0.02) and pre-pregnancy BMI (AdjOR 1.05, p< 0.0001). Smoking was associated with an AdjOR of 0.85 (non-significant),primipaternity multiparas were twice as likely to be smokers (23.8% vs 13.4%, p< 0.0001) compared with controls. AdjOR for primipaternity was 3.34 (p < 0.0001) indicating that primipaternity as risk belonged in the category of well-established risk factors like history of preeclampsia (11.2, p< 0.0001) and chronic hypertension (6.45, p< 0.0001). Conclusions Primipaternities in multiparae belongs to the major risk factors such as history of preeclampsia, chronic hypertension, multiple pregnancies while prolonged birth intervals belongs to moderate "regular physiological aging processes" such as increasing maternal age, parity or increasing pre-pregnancy BMI.